2019
DOI: 10.2147/ndt.s215289
|View full text |Cite
|
Sign up to set email alerts
|

<p>Conditioned taste aversion memory extinction temporally induces insular cortical BDNF release and inhibits neuronal apoptosis</p>

Abstract: Background: Memory extinction has been reported to be related to psychiatric disorders, such as post-traumatic stress disorder (PTSD). Secretion and synthesis of brain-derived neurotrophic factor (BDNF) have been shown to temporally regulate various memory processes via activation of tropomyosin-related kinase B (TrkB) receptors. However, whether memory extinction induces the synthesis and secretion of BDNF on the basis of its localization is not understood. In this study, we aim to investigate activity-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Those findings indicated that increases in the level of brain‐derived neurotrophic factor after exposure to social defeat stress might affect neural activities in the anterior cingulate cortex and insular cortex. Accordingly, blocking brain‐derived neurotrophic factor signaling within the insular cortex resulted in the reduction of c‐Fos expressions in the insular cortex and inhibited conditioned taste aversive responses in rats [64]. Our present results showed that stress contagion increased the brain‐derived neurotrophic factor level in the insular cortex but not in the anterior cingulate cortex, while both areas increased c‐Fos and FosB expressions.…”
Section: Discussionmentioning
confidence: 48%
“…Those findings indicated that increases in the level of brain‐derived neurotrophic factor after exposure to social defeat stress might affect neural activities in the anterior cingulate cortex and insular cortex. Accordingly, blocking brain‐derived neurotrophic factor signaling within the insular cortex resulted in the reduction of c‐Fos expressions in the insular cortex and inhibited conditioned taste aversive responses in rats [64]. Our present results showed that stress contagion increased the brain‐derived neurotrophic factor level in the insular cortex but not in the anterior cingulate cortex, while both areas increased c‐Fos and FosB expressions.…”
Section: Discussionmentioning
confidence: 48%